TEACHING ELF-AWARE PEDAGOGICAL STRATEGIES TO EMI PROFESSORS OF ARCHITECTURE - Pineda, Inmaculada (Estudos Linguísticos e Literários, 2020)
The internationalization process of Spanish universities has increased the need for teacher training courses to EMI professors. These training programs have a dual objective, to improve content lecturers’ linguistic skills in English as a Lingua Franca (ELF) and to develop methodological strategies that can facilitate the learning process in an academic setting. The current paper describes the implementation of a teacher training program developed at the University of Málaga designed for EMI professors of Architecture. The program had three phases: A Needs Analysis (NA) stage (2015), two teacher training courses (2015 & 2016), and a last stage was devoted to tracing the language progress and the attitudinal changes of the participants with regards to ELF and ELF-aware pedagogy (2016).